The role of physical activity in the treatment of type 2 diabetes - Balcerska, Kamila; Bielejewska, Marta; Ciecierska, Dominika; Wojtczak, Paweł; Gąsior, Paulina; Wrzesiński, Bartłomiej (Journal of Education, Health and Sport, 2018)
Type 2 diabetes belongs to the group of civilization diseases of the 21st century. In Poland, over 3 million people suffer from diabetes, including 1 million being undiagnosed. In the initial stage, this disease does not hinder functioning in everyday life, often people get to know about being affected by this disease during other diagnostic tests related to another illness. As diabetes develops, there may be numerous complications, including: retinopathy, nephropathy, neuropathy, cerebrovascular disease, ischemic heart disease, peripheral artery disease. Untreated type 2 diabetes can lead to death, so it is very important to start treatment quickly. The aim of therapy is to balance carbohydrate and lipid metabolism, achieve optimal blood pressure, proper body weight, and prevent complications. This can be achieved by combining a properly selected diet, physical activity and pharmacotherapy.